Does damming of the Colorado River affect the nursery area of blue shrimp Litopenaeus stylirostris (Decapoda: Penaeidae) in the Upper Gulf of California? - Aragón-Noriega, Eugenio Alberto (2000)
After damming the Colorado River the freshwater flow was reduced to 1 % of its virgin flow to the Upper Gulf of California (UGC). The ecological effects need to be properly documented. The UGC is the nursery area for Litopenaeus stylirostris, the most profitable fishery in the zone. In order to know the relative abundance of L. stylirostris postlarval stage we conducted a sampled survey every 14 days in 1993, 1994 and 1997, plus an intensive sampling during a complete tide cycle in July 1995 and 1996. We did 10 min trawls each hour during the flood tide. Relative abundance of postlarvae was higher (p<0.05) in those years when freshwater flow reached the UGC.